Primary "Brown Pigment" Bile Duct Stones. Issue 3 (1991) - Vitetta, Luis; Sali, Avni; Little, Peter; Nayman, Jack; Elzarka, Ayman
Abstract : Bile duct stones from 42 patients were morphologically and chemically analysed. The calculi from 27 patients had important primary bile duct stone (PBDS) features, consisting of a general ovoid shape and fragile structure, with alternating light and dark brown pigmented layers on cross-section. Chemically these stones contained low levels of cholesterol, with high levels of bilirubin and calcium. Subsequent infrared spectroscopy analysis showed that calcium bilirubinate and calcium palmitate were the only calcium salts present. Calcium palmitate was prominent in the light brown layers. A morphological and chemical comparison with gallbladder stones showed that bile duct "stasis stones" were similar in morphological and chemical composition to the brown pigment gallbladder calculi. However, they were distinct from most gallbladder stones, indicating that primary bile duct calculi have an aetiology that is different to 90% of gallbladder calculi. Primary bile duct calculi were observed to occur with or without the presence of a gallbladder, and more interestingly, in the bile duct of two patients with cholesterol gallbladder stones. Bile duct bile of patients with primary choledocholithiasis were always moderately to profusely infected and with abundant calcium bilirubinate precipitation. Moreover, this study has shown that PBDS chemical analyses profiles were consistent and correlated well with their defined morphology. Consequently, PBDS may be accurately identified at the time of operation by morphology. An important aetiological factor would appear to be infection, which would seem to promote bile duct bile stasis and eventual stone growth.